A COMPARATIVE ANALYSIS OF REGIONAL VARIETIES OF ENGLISH: Phonological, Lexical, and Lexicographical Perspectives (Ustozlar uchun, 2026)
The English language has evolved into numerous regional varieties across the globe, each distinguished by unique phonological, lexical, and grammatical features. This paper examines the major regional varieties of English — British, American, Australian, and Indian — through a comparative linguistic lens, with particular attention to pronunciation patterns, vocabulary differences, spelling conventions, and grammatical divergences. Additionally, the paper traces the historical development of regional lexicography in the United Kingdom, highlighting the pioneering contributions of scholars such as John Jamieson and Joseph Wright. Using descriptive and comparative analysis based on published linguistic scholarship, this study demonstrates that regional varieties of English, while mutually intelligible, reflect distinct socio-cultural identities. The findings underscore the importance of teaching World Englishes in contemporary language education and advocate for greater awareness of dialectal diversity in international communication contexts.